2013
DOI: 10.1371/journal.pone.0058057
|View full text |Cite
|
Sign up to set email alerts
|

Connexin43 Hemichannel-Mediated Regulation of Connexin43

Abstract: BackgroundMany signaling molecules and pathways that regulate gap junctions (GJs) protein expression and function are, in fact, also controlled by GJs. We, therefore, speculated an existence of the GJ channel-mediated self-regulation of GJs. Using a cell culture model in which nonjunctional connexin43 (Cx43) hemichannels were activated by cadmium (Cd2+), we tested this hypothesis.Principal FindingsIncubation of Cx43-transfected LLC-PK1 cells with Cd2+ led to an increased expression of Cx43. This effect of Cd2+… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 47 publications
(93 reference statements)
4
27
0
Order By: Relevance
“…Using this model, we confirmed our findings and explored the possible participation of the signaling cascades in Cd 2+ -induced cell injury. Consistent with our previous reports (Fang et al, 2011;Li et al, 2013), Cd 2+ caused release of ATP into the extracellular space in LLC-PK1 cells expressing EGFP-Cx43, which was significantly prevented by the hemichannel blockers heptanol and lindane (Fig. 6A), indicating an involvement of hemichannels.…”
Section: Extracellular Atp Suppresses Ampk Activationsupporting
confidence: 93%
See 3 more Smart Citations
“…Using this model, we confirmed our findings and explored the possible participation of the signaling cascades in Cd 2+ -induced cell injury. Consistent with our previous reports (Fang et al, 2011;Li et al, 2013), Cd 2+ caused release of ATP into the extracellular space in LLC-PK1 cells expressing EGFP-Cx43, which was significantly prevented by the hemichannel blockers heptanol and lindane (Fig. 6A), indicating an involvement of hemichannels.…”
Section: Extracellular Atp Suppresses Ampk Activationsupporting
confidence: 93%
“…Using an atomic force microscope, Muller and colleagues (Müller et al, 2002) observed that low extracellular Ca 2+ increased the outer pore diameter of hemichannels. Consistently, many investigators have found increased hemichannel permeability (Li et al, 2013;Stout et al, 2002). Here, we detected an increased exchange of small molecules across the cell membrane that was disrupted by blockade of Cx43-forming channels, indicating an involvement of hemichannels.…”
Section: +supporting
confidence: 89%
See 2 more Smart Citations
“…Further investigations demonstrated that inactivation of Cx43 eliminated PMA-induced mitochondrial protection. As the cardiomyocytes were cultured sparsely without cell to cell contact, the targeted inactivation of mtCx43 may have led to the suppression of PMA-induced mitochondrial protection (23,24). These results suggested that activation of PKCε may have attenuated mitochondrial dysfunction in a mtCx43-dependent manner.…”
Section: Discussionmentioning
confidence: 92%